Peran Sistem Informasi Akuntansi SDM dalam Meningkatkan Efisiensi Pengelolaan Karyawan: Sebuah Tinjauan Sistematis - Eka Jayanti, wantyjayanti@gmail.com; Irmayani, Windi (Jurnal Sistem Informasi Akuntansi, 2024)
This study aims to examine the role of human resource accounting information systems (HRIS) in improving employee management efficiency through a systematic review of the literature. Using the modified PRISMA method and Watase Uake tools, this study analyzed 9 selected scientific articles published between 2019-2023. The review results show that HR accounting information systems have a crucial role in improving employee management efficiency through several key aspects: (1) Integration of advanced technologies such as data analytics and blockchain that improve the accuracy and speed of HR information processing; (2) More effective data-driven decision-making related to employee recruitment, development, and retention; (3) More accurate measurement of performance and ROI for HR investments; (4) Increased transparency and accountability in HR management; (5) Optimization of human resource allocation that contributes to increased productivity and profitability. This study also reveals the importance of the integration of HR accounting information systems with the overall business strategy as well as the influence of system quality and user competence on the effectiveness of its implementation. These findings provide valuable insights for practitioners and researchers in the field of HR accounting and human resource management. In conclusion, HR accounting information systems prove to be a very important tool in improving the efficiency of employee management in this digital era. Further research is recommended to explore the integration of artificial intelligence in this system as well as its long-term impact on organizational performance.